An Economist's Perspective on Match-fixing and Self-sabotage in Contests. (July 2015) - Saha, Bibhas
In this note we provide an economist's perspective on self-sabotage in contests. When such self-sabotage is engineered at the behest of a third party for financial gains from betting markets, we see the twin problems of self-sabotage and betting corruption, which are known as the problem of match-fixing in sporting contests. We discuss the hidden incentives that different agents face in this environment. To curb match-fixing, legalization of betting would be a positive step followed by intelligent enforcement. Further, using a simple model we demonstrate that the risk of match-fixing diminishes with the number of teams involved in the contest.